(untitled) (Journal of Nepal Geological Society, 2002)
Pokhara Valley is an intramontane basin situated on the lap of southern foothills of Annapurna and Machhapuchhre Himal. The valley is surrounded by hills, which are mainly represented by low to medium grade metamorphic rocks. It is believed that the valley fill sediment s were derived from far north in the Himalaya, during three different catastrophic debris flow events along Seti River in Upper Pleistocene to Holocene Epoch. These sediments are rich in calcareous constituents and are susceptible to sinkhole and land subsidence hazards. Karstification is widespread in the form of sinkholes, caverns and sub-soil pinnacles in the Pokhara Valley. Such sinkholes and pinnacles are frequently observed in Ghachok Formation. Soil erosion and landslides are other natural hazards that frequently occur in steep terrain. As a result of heavy rainfall in monsoon, a number of new landslides occur and many old and dormant landslides become active. These landslides are the sources of huge amount of loose sediments that cause loss of lives, damages of public properties, infrastructures, and siltation in Phewa and Begnas lakes. Haphazard mining of river gravel and sand has also created the problem of riverbank erosion and flooding in the rainy season. Several earthquake events greater than 4 Richter scale have occurred in the past within the Pokhara Valley and its close proximity. Of these the largest earthquake events were 7 Richter scale in 1939 and 6.5 Richter scale in 1954 by which the Pokhara Valley suffered considerable damages. Unplanned urbanization, haphazard development of infrastructures and settlements, improper locations of industries, improper landuse, uncontrolled surface drain, haphazard disposal of municipal waste etc. are the root causes of environmental degradation in Pokhara Sub-Metropolitan. All types of hazard prone areas are identified and categorized as low, medium and high hazard areas in Engineering and Environmental Geological map of the Pokhara Valley. The proposed recommendations are expected to be useful to the users in protecting environment and mitigating disaster.